Granulometric effect of silica nanoparticles on hydration kinetics and microstructure of cement based materials. Issue 3 (17th February 2023) - Sharma, U.; Solanki, A.; Singh, L.P
Abstract: Effect of particle size of two types of silica nanoparticles (SNPs) on hydration kinetics of tricalcium silicate (C3 S) and Portland cement was investigated. Two different types of SNPs were used in the present study, first one is the synthesized by sol-gel method (SNPs-sg) having particle size 30–70 nm, while the second one is the synthesized by Flame Spray Pyrolysis method (SNPs-fsp) having particle size <10 nm. The dosages of SNPs used in this study varied from 1–10% and water/binder ratio used for the hydration was 0.4. Rietveld analysis of XRD results show that at 4 h of hydration, the unhydrated content in control samples at 4 h hydration was ∼88% and in presence 1% SNPs-sg, it was ∼75%, however, in presence of SNPs-fsp, the content of unhydrated C3 S was ∼60%. Further, FTIR results reveal that in case of control samples at 1 h of hydration, the characteristic peaks of C3 S at 850 cm −1 and 940 cm −1 are present, while, with 1% SNPs-sg addition, reduction in the intensity C3 S peaks were observed showing acceleration in dissolution rate and a broader peak is observed at ∼1110 cm −1 with 1% SNPs-fsp samples indicating the starting of polymerization in silicate chain of C-S-H gel.